Cholesterol-binding capacity and solubility of the undigested fraction of soybean protein - Gatchalian-Yee, M.; Yamada, K.; Sugano, M.; Ishizuka, C.; Yunoki, S. (1999)
Very little is known of some properties of the undigested fraction (UDF) of soybean protein isolate, a cholesterol-lowering agent. This study was conducted to determine some properties of UDF which may explain its hypocholesterolemic reaction. Results revealed that UDF from soybean protein had the highest binding capacity compared to protein isolates from 22 plant sources. Increasing the pH of the methanol-treated UDF up to 12 increased its solubility. Increased level of ammonium sulfate in the buffer in which methanol-treated UDF was suspended, improved the binding capacity of UDF. In the attempt to purify UDF, use of TSK gel SP and DEAE Toyopearl ion exchange resin, brought about recommendable results.
Keywords: Soybean -- Nutrition; Cholesterol